Śāntiniketanera eka yuga - Datta, Hirendranath, 1903- (Biśvabhāratī Granthanabibhāga, 1980)
Author's reminiscences of and writings on educationists and social activists of Santiniketan, educational center founded by Indian poet Rabindranath Tagore, 1861-1941.